How Does F1-ATPase Generate Torque?: Analysis From Cryo-Electron Microscopy and Rotational Catalysis of Thermophilic F1 - Noji, Hiroyuki; Ueno, Hiroshi (Frontiers in Microbiology, 2022)
The F1-ATPase is a rotary motor fueled by ATP hydrolysis. Its rotational dynamics have been well characterized using single-molecule rotation assays. While F1-ATPases from various species have been studied using rotation assays, the standard model for single-molecule studies has been the F1-ATPase from thermophilic Bacillus sp. PS3, named TF1. Single-molecule studies of TF1 have revealed fundamental features of the F1-ATPase, such as the principal stoichiometry of chemo-mechanical coupling (hydrolysis of 3 ATP per turn), torque (approximately 40 pN·nm), and work per hydrolysis reaction (80 pN·nm = 48 kJ⁄mol), which is nearly equivalent to the free energy of ATP hydrolysis. Rotation assays have also revealed that TF1 exhibits two stable conformational states during turn: a binding dwell state and a catalytic dwell state. Although many structures of F1 have been reported, most of them represent the catalytic dwell state or its related states, and the structure of the binding dwell state remained unknown. A recent cryo-EM study on TF1 revealed the structure of the binding dwell state, providing insights into how F1 generates torque coupled to ATP hydrolysis. In this review, we discuss the torque generation mechanism of F1 based on the structure of the binding dwell state and single-molecule studies.